Digitizing Cultural Heritage: Augmented Reality for Education and Visualization of Local Wisdom in Ikat Woven Fashion - Weo, Napsiyana Asti; Selan, Rima N.; Ada Manu, Ariency Kale; Manu, Sarlince O.; Fathurrahmaniah, Fathurrahmaniah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The ikat woven fabric of East Nusa Tenggara (NTT) represents one of Indonesia’s intangible cultural heritages, rich in philosophical values, symbolism, and local wisdom. Rumah Tenun Ina Ndao in Kupang City plays a significant role in preserving and promoting ikat weaving traditions; however, it continues to face challenges in cultural education and market expansion. Conventional educational methods and suboptimal marketing strategies have made information about the meanings of motifs, philosophies, and production processes of ikat fabrics less accessible to the public.This Community Partnership Program (PKM) offers an innovative solution through the application of Augmented Reality (AR) technology based on QR Codes, utilizing the MyWebAR web platform. The AR technology provides an interactive visual experience through 3D objects, animations, and audio to convey the meanings and philosophies of ikat motifs from various regions of NTT, as well as the traditional weaving processes embedded with cultural values.The implementation methods include socialization, training, technology application, mentoring, and continuous evaluation. Consumers who scan the QR Code on products or promotional media gain an engaging educational experience—allowing them to view the motifs, understand the stories behind them, and virtually witness the weaving process. This enhances both cultural appreciation and consumer interest.The expected outcomes of this program include increasing public knowledge of local cultural heritage, strengthening the marketing of ikat woven products in local and global markets, and preserving NTT’s cultural legacy. The program outputs consist of scientific publications, mass media publications, and documentary videos to support the promotion and cultural education of NTT ikat weaving in a broader and more sustainable manner.